Temporally interfering TMS: focal and dynamic stimulation location - Memarian Sorkhabi, M; Wendt, K; Denison, T (IEEE, 2020)
In this study, we present a temporal interference (TI) concept to achieve focal and steerable stimulation in the targeted brain area through transcranial magnetic stimulation (TMS). This method works by inducing two high-frequency electric fields with a slight frequency difference via two independent coils. The intrinsic nonlinear nature of the nerve membrane, which acts as a low-pass filter, does not allow the nerve to engage at high frequencies. Instead, neurons at the intersection of two electric fields can follow the frequency difference of the two fields. For 3D MRI-derived head models, the finite element method is used to compute the electric field induced by the time-varying magnetic field along with the electric field penetration depth and the activated volume for the specific coil parameters. A deeper stimulation with an acceptable spatial spread can be obtained by controlling the intersection of the fields by finding the optimal position and orientation of the two coils. Moreover, by changing the voltage ratio of the coils, and not their mechanical orientation, the intended area can be dynamically driven. The computational results show that the TI technique is an efficient approach to resolve the electric field depth-focality trade-off, which can be a reasonable alternative to complex coil designs. The system proposed in this paper shows a great promise for a more dynamic and focused magnetic stimulation.